Metabolomics studies on Solanaceae members under abiotic stress: A review - Vadakkemuriyil, D N; Rahul, T; Sharma, A; Joseph, J; Manoti, S; Sunidhi; Saini, Khem Chand (Plant Science Today, 2026)
Plants are known to face various abiotic stresses, which lead to reduced yield. It has been reported that metabolite concentrations vary under different abiotic stress conditions. Metabolomic studies are widely used to analyse the compositions of various metabolites. Metabolomic studies utilise different methods such as gas chromatography (GC), liquid chromatography (LC) in combination with mass spectrometry (MS) and nuclear magnetic resonance (NMR) to analyse metabolites. The complete set of low-molecular weight metabolites present in the cell constitutes the metabolome. The amino acid proline is a major metabolite present in most stressed plants. Plant tissues exhibit altered amino acid and sugar levels under stress. As with other plant groups, similar responses are observed in members of the Solanaceae family. When solanaceous plants are subjected to stress, their cell activates the antioxidant systems to eliminate reactive oxygen species (ROS) produced in response to stress. Reactive oxygen species are scavenged by enzymatic antioxidants such as superoxide dismutase (SOD) and peroxidase (POD), as well as by non-enzymatic antioxidants, including flavonoids and ascorbic acid.